Investigation of the transport processes controlling the geographic distribution of carbon monoxide at the tropical tropopause. Issue 5 (9th March 2015) - Jensen, E. J.; Pfister, L.; Ueyama, R.; Bergman, J. W.; Kinnison, D.
Abstract: Convectively influenced trajectory calculations are used to investigate the impact of different Tropical Tropopause Layer (TTL) transport pathways for establishing the distribution of carbon monoxide (CO) at 100 hPa as observed by the Microwave Limb Sounder (MLS) on board the Aura satellite. Carbon monoxide is a useful tracer for investigating TTL transport and convective influence because the CO lifetime (≃1–2 months) is comparable to the time required for slow ascent through the TTL. MERRA horizontal winds are used for the diabatic trajectories, and off‐line calculations of TTL radiative heating are used to determine the vertical motion field. The locations and times of convective influence events along the trajectories are determined from 3‐hourly, geostationary satellite measurements of convective clouds. The trajectory model reproduces most of the prominent features in the 100 hPa CO geographic distribution indicated by the MLS observations for the winter and summer 2007 periods simulated. CO concentrations and tendencies simulated with the Whole Atmosphere Climate Chemistry Model (WACCM) are used to specify boundary‐layer concentrations for convective influence and CO loss rates resulting from reaction with OH. The broad maximum in CO concentration over the Pacific during Boreal winter is primarily a result of the strong radiative heating (corresponding to upward vertical motion) associated with the abundant TTL cirrus in this region. Convection over the Pacific brings clean maritime air to the tropopause region and actually decreases the 100 hPa CO. The relative abundance of CO over the continental convective regions during wintertime is sensitive to small variations in convective cloud‐top height. Both the simulated and the observed summertime 100 hPa CO distributions are dominated by the maximum co‐located with the upper level anticyclone forced by the Asian monsoon convection. Sensitivity tests indicate that the summertime Asian monsoon anticyclone 100 hPa CO maximum is dominated by extreme convective systems with detrainment of polluted air above about 360–365 K potential temperature. This result stems directly from the fact that the heating rates are negative (downward motion) below 360–365 K during summertime through most of the tropics; therefore, air detrained from convection at lower levels will generally just sink back down into the middle troposphere. We find that most of the CO feeding into the Asian monsoon anticyclone comes from convection over the Tibetan Plateau and India, with relatively minor contributions from southeast Asia and eastern China. Key Points: Highest tropical convection controls tropical tropopause CO Tropical tropopause heating rate distribution affects tracer distribution Tibetan Plateau convection is important for Asian anticyclone CO concentration